Water Turbine Simulation using Autodesk Simulation CFD - Suwarsono Suwarsono; Budiono Budiono (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2017)
The need on electricity increases annually while its supply decreases, meanwhile power plant has not increased. Process of building microhydro power plant needs scientifically experience and more time to give suitable result as it designed. Sengkaling Cross-flow Microhydro power plant resulted inappropriate electricity power compare with designed power plant. The design is mostly not in accordance with planned calculation. It is caused by the engineer who is not considering surrounding condition. Therefore, simulation is very important to be conducted that it only needs short time to the design maximally arranged. By simulation, building and assembling process can be conducted faster and decreases error risks. Simulation for this research used AUTODESK SIMULATION CFD.